Nonlinear State-Space Representations of a Quadrotor through Bond-Graph Technique - Omurlu, Vasfi E.; Sagirli, Ahmet; Haskoy, Ertan (IEEE, 2012)
Obtaining efficient dynamic equations of complex systems, like processes or robotic systems, are very important for control system design. While various forms of acquiring motion equations exist, state-space form has its advantages for analyzing complex systems. Among analytical and graphical techniques of finding dynamic behavior of a system, bond-graph provides straight forward way of serving linear/nonlinear equations of systems in state-space form. In this study, a four-propeller-actuated full/reduced order quadrotor spatial dynamics are investigated by using bond-graph technique. Full order dynamic behavior is obtained including motor, gear, shaft, propellers and the body. Additionally, neglecting motor dynamics, reduced order state-space representations of the system is also provided, assuming force/moment input and propeller speed as inputs to the vehicle separately. Responses of the models are compared and discussed.
Keywords: Bond Graph; Nonlinear Equations; Dynamic Modelling; Differential Equations; State Space; Automation & Control Systems; Engineering